Pengabdian Guru dalam Meningkatkan Keterampilan Berbicara Siswa Menggunakan Metode Ceramah - Maqfiroh, Fika; Husni, Muhammad (Belalek, 2025)
Speaking ability can be defined as linguistic capacity or a means of communication whereby a person can convey ideas or information in a logical sequence and master the mechanisms of speaking conventions (pronunciation, grammar, vocabulary, fluency, and comprehension). In this study, the researcher applied the lecture method to solve the problems faced by students. This research was conducted in order to improve students' speaking skills through lecture techniques in public speaking extracurricular classes at Madrasah Tsanawiyah Tarbiyatusshibyan. In conducting this research, the researcher used descriptive qualitative methods with case studies. To achieve the expected conclusions, appropriate strategies are needed so that good language comprehension can improve students' public speaking skills, and technical preparation is needed in the learning process. For example, students were given texts to speak from and received guidance from teachers before delivering their speeches. The results of the implementation showed that in a short period of time, students were able to speak well. Not only that, but this method also made students more confident.